Research Progress on the effect of radiotherapy on immune function of tumor patients - Li, Wenxin; Yu, Xiaolei; Li, Qingshan; Xu, Fan; Zhang, Sheng Lin; Li, Xiao (Nepalese Journal of Cancer, 2022)
With the cure rate of 21%, radiotherapy is one of the most effective methods for tumor treatment, and about 70% of solid tumors need radiotherapy.With the in-depth study of human impact by radiotherapy and immune system and tumor microenvironment, radiotherapy is no longer used as a local treatment. It is found that irradiation of tumor can activate body immunity. There exist two different views: one is that radiotherapy inhibits immunity, because it can kill tumor cells and normal cells at the same time.The other is that radiotherapy promotes immunity, causing tumor cell necrosis or apoptosis, releasing immune cytokines or promoting immune cell activation, and bystander effect. In recent years, the idea of radiotherapy promoting immunity has been more and more supported by literatures. Whether radiotherapy promotes or inhibits immunity is a research hot spot in recent years. This paper reviews the research progress of the effect of radiotherapy on immune function of tumor patients.